2015
DOI: 10.1017/s1751731115001731
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits and meat fatty acid composition of Barbarine lambs reared on rangelands or indoors on hay and concentrate

Abstract: The objective of this study was to compare carcass and meat quality between Barbarine lambs raised on rangelands and those reared indoors. A total of 24 weaned male lambs (23.2 kg) were allotted into two groups. The first group (GS) grazed pasture dominated by natural shrubs and was supplemented with 100 g of concentrate. The second group (HS) received oat hay and 200 to 300 g supplement of the same concentrate in order to obtain the same average daily gain (ADG) as the GS group. Six lambs from each group were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…They accounted for 70 %-80 % of the total FA. These results were consistent with values commonly accepted for fat-tailed (Majdoub-Mathlouthi et al, 2015;Mekki et al, 2016) and thin-tailed sheep (Joy et al, 2012;Hopkins et al, 2014).…”
Section: Resultssupporting
confidence: 92%
“…They accounted for 70 %-80 % of the total FA. These results were consistent with values commonly accepted for fat-tailed (Majdoub-Mathlouthi et al, 2015;Mekki et al, 2016) and thin-tailed sheep (Joy et al, 2012;Hopkins et al, 2014).…”
Section: Resultssupporting
confidence: 92%
“…Tissues of adults have a lower rate of synthesis of n-3 long-chain PUFAs than those of infants, so the LA/ALA ratio in the diet does not have too much of an impact on adults. In the literature we reviewed, the LA/ALA ratio was used in research on ruminants and dairy products as well [ 43 , 55 , 109 ]. Majdoub-Mathlouthi et al compared the meat fatty acid composition of Barbarine lambs raised on rangelands and those reared indoors.…”
Section: Nutritional Indicesmentioning
confidence: 99%
“…Majdoub-Mathlouthi et al compared the meat fatty acid composition of Barbarine lambs raised on rangelands and those reared indoors. The results showed that the grazing lambs had lower LA/ALA [ 43 ]. Sharma et al compared the fatty acid profile of indigenous Indian cow milk with exotic and crossbred counterparts.…”
Section: Nutritional Indicesmentioning
confidence: 99%
“…The very small difference (less than 1% unit) in water content (Table 2) has also not influenced the juiciness perception of the meat of the different groups, which is consistent with most of the previous research not reporting any difference in meat juiciness between concentrate or grassfed lambs (Fisher et al 2000;Borton et al 2005;Resconi et al 2009) although Priolo et al (2002) found that meat from stall lambs fed 85% and 15% hay was juicier than for grazed lambs. In many studies, stall feeding is confounded with concentrate feeding or conserved forage feeding (Procha et al 2009;Majdoub-Mathouthi et al 2015). In the present study, fresh grass was either grazed (GR) or stall fed (ZGR), allowing comparison between indoor lambs and those exposed to environmental conditions, such as exercise, outside temperature, rain, and insect.…”
Section: Sensory Evaluationmentioning
confidence: 99%